PENGEMBANGAN MODEL KEBIJAKAN BEHAVIOUR SAFETY CULTURE DALAM RANGKA PENINGKATAN KEAMANAN DAN KESEHATAN LINGKUNGAN KERJA - Eko Prasetyo; Sri Wahyuningsih (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2014)
Quality of health and the occupational environment is an important factor for achieving high productivity in order to achieve optimal business profits. From preliminary surveys in PT.Pura Barutama in the know that there is a work accident and the company has a potential risk of80% in case of fire due to raw materials, production processes, and products of the paper isflammable. This study aims to describe the knowledge, attitude, practice and development ofthe Behaviour of Safety Culture Policy in order to improve work safety and health of theneighborhood. This type of research is qualitative design method Action Research by thenumber of 12 informants. The survey results revealed that the description of the knowledgeworkers of the Occupational Health and Safety (K3) The company is still lacking, K3orientation only for safety and productivity company, workforce attitudes picture onOccupational Health and Safety (K3) in the company strongly supports the K3 programimplemented in the company. Overview of program implementation practices OccupationalHealth and Safety (K3) in the company has been good, in accordance with the principles andapplication of SMK3 and P2K3, Safety Cultural policy development based discovery stillUnsafe Action in the company. Development of cultural policy model K3 to become a necessityin the company by way of, among others: management commitment, experts K3 move, planningprograms - programs K3, K3 program implementation, evaluation and support of thegovernment. Keywords: Occupational Health and Safety; Safety Culture; K3 program.